Thursday

March 5, 2015

March 5, 2015

Posted by **Anonymous** on Tuesday, March 26, 2013 at 3:32pm.

27x-3(x-6)= 6

F: -2

G: -1/2

H: 1/2

J: 2

- algebra -
**Ms. Sue**, Tuesday, March 26, 2013 at 3:39pm27x-3(x-6)= 6

27x - 3x + 18 = 6

24x = 6 - 18

24x = - 12

x = -0.5

- algebra -
**Anonymous**, Tuesday, March 26, 2013 at 3:43pmthank you soo much

- algebra -
**Ms. Sue**, Tuesday, March 26, 2013 at 4:31pmYou're very welcome.

**Answer this Question**

**Related Questions**

Algebra (Intermediate) - 5. Solve using the elimination method. Show your work. ...

Math - Logarithmic - Solve: 2log_3(x) - log_3(x-2) = 2 My Work: log_3(x^2) - ...

Math - factorize the following using. formula #1 : (x+y)^3 = x^3+3x^2y+3xy^2+y^2...

maths - quadratic equation solve the equation by factorization 27x^2 - 126x = 0 ...

math - solve the equation for x using the fact that if a^u =a^v then u=v. 9^-x+...

Algebra 1--Please, help me! - Solve the following equation by graphing the ...

Algebra story problem - I need to turn this story into an algebra problem: Your ...

Math - [(6x+1)^3][(27x^2+2)-(9x^3+2x)](3)[(6x+1)^2](6) over [(6x+1)^3]^2 Help me...

Algebra 1 - Solve the following equation by graphing the related function. 1. ...

math, algebra - How do I solve for the following: Directions solve each literal ...